Driving Forces of Landscape Pattern Evolution due to Land Use Changes in the Kambang Iwak Kecik Catchment, Palembang - Muthmainah, Nyimas Atika Marwiyah; Putranto, Dinar Dwi Anugerah; Juliana, Imroatul Chalimah (Fakultas Teknik Universitas Tanjungpura, 2025)
Rapid urban development in Palembang has significantly increased surface runoff due to reduced infiltration areas, raising flood risks in low-lying zones. The Kambang Iwak Kecik Retention Pond plays a critical role in capturing runoff from its surrounding catchment. This study identifies the contributing watershed areas and estimates flood discharges under design rainfall conditions. A GIS-based approach delineated seven sub-watersheds using Digital Elevation Model (DEM) data and flow direction analysis. Design rainfall intensities for return periods of 2